The effect of mitochondrial DNA polymorphisms on cattle reproduction - Alves, Jackeline Santos; Diaz, Iara Del Pilar Solar; da Cruz, Valdecy Aparecida Rocha; Bastos, Marisa Silva; de Oliveira, Louise Sarmento Martins; de Albuquerque, Lucia Galvão [UNESP]; de Camargo, Gregório Miguel Ferreira; Costa, Raphael Bermal (Springer Nature, 2021)
The aim of this study was to identify SNPs located in mitochondrial DNA that are associated with reproductive traits in beef cows. A total of 1999 Nelore females genotyped with the high-density Illumina BovineHD BeadChip (Illumina Inc., San Diego, CA, USA) were used to study the association of mitochondrial DNA variants with reproductive traits using a single-step procedure. In a preliminary analysis, the present results indicate a small participation of the mitogenome in the expression of reproductive traits in beef cattle. However, possible difficulties related to the biological characteristics of mitochondrial DNA and its inheritance, genotyping, and annotation of the phenotypes studied may also explain the results.
Keywords: Bos taurus indicus; Fertility; Nelore; Sexual precocity; SNP